Highly enantioselective δ-protonation and formal [3 + 3] annulation promoted by N-heterocyclic carbene. Issue 11 (27th April 2022) - Dong, Mengdie; Duan, Xiao-Yong; Li, Yanting; Liu, Binghao; Qi, Jing
Abstract : A chiral NHC catalyst reacts with α, β-γ, δ-diunsaturated aldehydes to generate an extended Breslow intermediate. Upon δ-protonation and tautomerization, the resulting α, β-unsaturated acyl azolium undergoes [3 + 3] annulation with enamines to afford various dihydropyridinones. Abstract : An N-heterocyclic carbene (NHC) catalyzed highly enantioselective δ-protonation of α, β-γ, δ-diunsaturated aldehydes is described. In this work, a chiral NHC catalyst reacts with α, β-γ, δ-diunsaturated aldehydes to generate the extended Breslow intermediate. Upon highly enantioselective δ-protonation and tautomerization, the resulting α, β-unsaturated acyl azolium undergoes a [3 + 3] annulation with enamines to afford various dihydropyridinones with excellent enantioselectivities and good yields (up to 99% ee). This unique intermediate also provides access to δ-chiral esters with potential enantioselectivities.